Dielectrophoretic trapping of nanoparticles with an electrokinetic nanoprobe. Issue 13 (11th June 2013) - Wood, Nicholas R.; Wolsiefer, Amanda I.; Cohn, Robert W.; Williams, Stuart J.
<x xml:space="preserve">Abstract</x> A high aspect ratio 3D electrokinetic nanoprobe is used to trap polystyrene particles (200 nm), gold nanoshells (120 nm), and gold nanoparticles (mean diameter 35 nm) at low voltages (<1 Vrms). The nanoprobe is fabricated using room temperature self‐assembly methods, without the need for nanoresolution lithography. The nanoprobe (150–500 nm in diameter, 2–150 μm in length) is mounted on the end of a glass micropipette, enabling user‐specified positioning. The nanoprobe is one electrode within a point‐and‐plate configuration, with an indium–tin oxide cover slip serving as the planar electrode. The 3D structure of the nanoprobe enhances dielectrophoretic capture; further, electro‐hydrodynamic flow enhances trapping, increasing the effective trapping region. Numerical simulations show low heating (1 K), even in biological media of moderate conductivity (1 S/m).